La anécdota como estrategia para mejorar la expresión oral - Samillan Llontop, Claudia Cynthia (2021)
The present work of professional sufficiency entitled "The anecdote as a strategy to improve oral expression", has been designed and executed with the students of the fifth grade of primary education. Its purpose is to promote anecdotes as a resource that leads to improving the competence of oral communication in our students, through a dynamic interaction between one or more interlocutors to express and understand ideas and emotions, therefore, this work This research is proposed considering our experience from the task in the classroom, where we can appreciate those difficulties or strengths that our students are presenting in relation to oral expression, for this the theoretical contributions referred to the characteristics of the Oral expression with emphasis on the proposal of the anecdote as a strategic resource for the achievement of the competence. In the pedagogical support, the contributions of the curricular planning guides were considered, as well as the pedagogical processes that were applied in the learning session, as well as the didactic processes of oral communication, considering in all these processes the adequate planning, the revision of the same in its implementation, as well as the application of the evaluation from the formative approach towards the continuous improvement of the students through practice; Vygotsky's contributions since he recognizes that oral language is a social product and has its origin independently of thought, and in the development of the activity it is a companion of the action; However, these discoveries go hand in hand with a context of collaborative dialogue between the teacher and students. Therefore, we affirm that the methodology selected and applied in this learning session was totally active, the students participated actively by telling their anecdotes, which as we mentioned before, this activity allowed us to identify the problems that the students present individually in their communicative expressions, the organization of their ideas, their vocabulary, as well as the use of non-verbal and paraverbal resources, for this we propose to promote the solution of the problem in part the strategy of telling anecdotes, which permanently aroused the interest of students for know those personal situations through their experiences, promoting in them dialogue, collaboration and creative expression and their abilities as speakers.